Digital student ID card using NFC technology - Eng, Mun Shuen (2022)
Most of the education institution, student and lecturer are given an identity card that could identify themselves. It is important to protect the personal information data on the card from identity thief in this era of big data. Besides, traditional Identity Card management is inefficient. Education institution which still using traditional ID card will waste a lot of resources on managing the cards. Not to mention that the ID card could not be reused, cause a lot of harm to the environment. Student ID card are designed to perform multiple functions. One of the functions is to take class attendance. Some institution uses different types of attendance taking method and these methods have their disadvantages. This mobile android application project is designed to replace the traditional ID card. This application will give users a more secured authorized identity in the education institution area by registering each device’s unique Android ID. Besides, this application provides attendance management function for admin and attendance taking function for student and lecturer. NFC technology will be implemented to become the attendance taking method. NFC technology is not only safe, but also could utilize the attendance taking process. Most importantly, it could increase the attendance rate and improve the attendance data accuracy. This application will be developed using Android Studio IDE and Firebase cloud database.